Learning to see in 3D with two eyes: the role of experience, plasticity and neurochemistry - Ip, B; Bridge, H (Portland Press, 2020)
Humans, along with other predators, have forward-facing eyes which restrict the area of the world that can be seen when compared to animals with eyes on the side of the head. Why would we sacrifice this panoramic vision? The answer is the very precise ability that having two eyes with overlapping and slightly different viewpoints provides to determine fine differences in depth. While interpreting this type of ‘binocular depth’ appears effortless, the precise calculations necessary for perceiving binocular depth require significant computational power in the cerebral cortex and the fine tuning of neurochemical interactions. This processing occurs in the visual regions of the brain and must be honed through early experience for accurate performance. By considering each stage of binocular processing and the neurochemical interactions required for integrating signals from the two eyes, we can begin to understand how the inherent ability of the brain to learn might help us when binocular vision goes wrong.